Bone marrow type 2 innate lymphoid cells: a local source of interleukin‐5 in interleukin‐33‐driven eosinophilia - Johansson, Kristina; Malmhäll, Carina; Ramos‐Ramírez, Patricia; Rådinger, Madeleine (Immunology, 2018)
Summary T helper type 2 (Th2) cells, type 2 innate lymphoid cells (ILC2s) and eosinophil progenitors have previously been described to produce interleukin‐5 (IL‐5) in the airways upon allergen provocation or by direct administration of IL‐33. Eosinophilic airway inflammation is known to be associated with IL‐5‐dependent eosinophil development in the bone marrow, however, the source of IL‐5 remains unclear. T helper cells, ILC2s and CD34+ progenitors have been proposed to be involved in this process, therefore, we investigated whether these cells are taking part in eosinophilopoiesis by producing IL‐5 locally in the bone marrow in IL‐33‐driven inflammation. Airway exposure with IL‐33 led to eosinophil infiltration in airways and elevated eotaxin‐2/CCL24. Importantly, IL‐5 production as well as expression of the IL‐33 receptor increased in ILC2s in the bone marrow under this treatment. A small but significant induction of IL‐5 was also found in CD34+ progenitors but not in T helper cells. Similar results were obtained by in vitro stimulation with IL‐33 where ILC2s rapidly produced large amounts of IL‐5, which coincided with the induction of eosinophil hematopoiesis. IL‐33‐mediated eosinophil production was indeed dependent on IL‐5 as both airway and bone marrow eosinophils decreased in mice treated with anti‐IL‐5 in combination with IL‐33. Interestingly, the responsiveness of ILC2s to IL‐33 as well as IL‐33‐induced eotaxin‐2/CCL24 were independent of the levels of IL‐5. In summary, we demonstrate for the first time that IL‐33 acts directly on bone marrow ILC2s, making them an early source of IL‐5 and part of a process that is central in IL‐33‐driven eosinophilia. Type 2 innate lymphoid cells (ILC2s) in the mouse bone marrow express high levels of the interleukin‐33 (IL‐33) receptor ST2. These cells rapidly produce large amounts of IL‐5 upon IL‐33 stimulation, which results in expansion of CD34+ IL5Rα+ eosinophil progenitors in vitro. This novel finding identifies IL‐5‐producing bone marrow ILC2s as a new important mediator of IL‐33‐driven eosinophil development.